Non-abstinent treatment outcomes for cannabis use disorder. (1st August 2021) - Levin, Frances R.; Mariani, John J.; Choi, C. Jean; Basaraba, Cale; Brooks, Daniel J.; Brezing, Christina A.; Pavlicova, Martina
Highlights: Abstinence is often a primary outcome for Cannabis Use Disorder clinical trials. It is reasonable to reconsider whether abstinence should be the primary outcome. This study explored reduction in self-reported days of use as a viable outcome. Two studies that were not promising looking at abstinence were reanalyzed, similar to a recently completed trial. In all three trials, those on medication were more likely to move from heavy to moderate use during the course of the trial. Abstract: Background: Abstinence remains a standard outcome for potential treatment interventions for Cannabis Use Disorder (CUD). However, there needs to be validation of non-abstinent outcomes. This study explores reductions in self-reported days of use as another viable outcome measure using data from three completed randomized placebo-controlled clinical trials of pharmacological interventions for CUD. Methods: The three trials tested the effect of quetiapine (QTP, n = 113); dronabinol (DRO, n = 156); and lofexidine + dronabinol (LFD, n = 122). Self-reported cannabis use was categorized into three use-groups/week: heavy (5–7 days/week), moderate (2–4 days/week) and light use (0–1 days/week). Multinomial logistic regressions analyzed the treatment by time effect on the likelihood of light and moderate use compared to heavy use in each study. Results: Across the three trials, there was no significant overall time-by-treatment interaction (QTP: p = .06; DRO: p = .15; LFD: p = .21). However, the odds of moderate compared to heavy use were significantly higher in treatment than in placebo groups starting around the midpoint of each trial. No treatment differences were found between the odds of light compared to heavy use. Conclusions: While study-end abstinence rates have been a standard treatment outcome for CUD trials, reduction from heavy to moderate use has not been standardly assessed. During the last several weeks of each trial, those on active medication were more likely to move from heavy to moderate use, which suggests that certain medications may be more impactful than previously assessed. Future studies should determine if this pattern is associated with less CUD severity and/or improved quality of life.